Exchange Autotransfusion for Rapid Correction of Hyperkalemia During Liver Transplantation: A Case Report. Issue 1 (1st January 2019) - Yoon, Uzung; Gerney, Garrett; Hsu, George; Elia, Elia; Kang, Yoogoo
Abstract : A 46-year-old woman with alcoholic cirrhosis and hepatorenal syndrome requiring hemodialysis presented with hyperkalemia (5.5 mEq/L) immediately before liver transplantation. For correction of hyperkalemia, an exchange transfusion began by removing her blood into an autotransfusion system to wash out noncellular components while maintaining normovolemia. Additionally, she received washed homologous red blood cells, insulin, and glucose to minimize or reduce the degree of hyperkalemia. Serum potassium level decreased to 4.0 mEq/L within 3 hours and was 5.0 mEq/L 30 seconds after reperfusion of the grafted liver. Postreperfusion syndrome was not observed. In summary, exchange transfusion was used successfully for rapid correction of hyperkalemia, showing the value of its application in liver transplantation.